ANALISIS PENILAIAN PERUSAHAAN PADA SEKTOR PERBANKAN YANG TERDIVERSIFIKASI(STUDI KASUS PERUSAHAAN PERBANKAN GO PUBLIK 2013-2014) - NURAIDA N, SEALLY (Jurnal Akuntansi AKUNESA, 2015)
Various companies have to diversify in an effort to improve company performance. This study measures the value of the company after diversifying by using Tobin's Q and also in terms of size. Diversification of the banking sector lately is needed in this case because of the risk of congenital owned high enough. This study proves that the assessment of the banking industry are listed on the Stock Exchange 2013-2014 increased in line with the company's increasingly diversified.Keywords: Diversification, Tobin’s Q, Size